New generations and the labor market: Challenges in current educational relevance - Gómez Muñiz, Magdiel; Díaz Thomé Yániz, Luis Rodrigo; Herrera Ávila, Juan Manuel (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: Identify the challenges of Higher Education Institutions (HEI) in the relevance of the educational offer and its correspondence with the liking and preferences of the new generations with respect to university degrees demanded by the labor market. Method: This discussion is relevant and pertinent due to the findings obtained with the application of a quantitative methodology in an in-depth intervention-action study whose indicators are based on the perceptions of 600 high school students. Originality / contribution: all those grouped in the category of new generations are considered as generation Z.  Generation T is left out because of their age and educational stage. Information gathering: 100 private sector employers or entrepreneurs in Guadalajara, Jalisco participated in this study. Conclusions: it is possible to identify necessary university degrees for this sector, with respect to 44 programs currently offered by the HEI of the Guadalajara Metropolitan Area